2017
DOI: 10.3389/fenrg.2017.00005
|View full text |Cite
|
Sign up to set email alerts
|

Saccharification of Agricultural Lignocellulose Feedstocks and Protein-Level Responses by a Termite Gut-Microbe Bioreactor

Abstract: This study investigated saccharification and protein-level responses to the candidate biofuel feedstocks corn stover (CS) and soybean residue (SR) by the gut of a lower termite. The focus termite was Reticulitermes flavipes, which is a highly efficient digester of wood lignocellulose that houses a mixture of prokaryotic and eukaryotic microbes in its gut. Our specific objectives were to (i) measure saccharification potential of the CS and SR feedstocks by termite gut protein extracts, (ii) identify specific pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Little information is available concerning implementation and taming of insect guts microbiomes as a whole in bioreactors. Some articles related to utilization of termite guts protein extracts ( Rajarapu and Scharf, 2017 ) or microbiomes as a whole ( Hamdi et al, 1992 ; Auer et al, 2017 ) but to our knowledge no information could be found concerning other type of insects implemented in bioreactors.…”
Section: Resultsmentioning
confidence: 99%
“…Little information is available concerning implementation and taming of insect guts microbiomes as a whole in bioreactors. Some articles related to utilization of termite guts protein extracts ( Rajarapu and Scharf, 2017 ) or microbiomes as a whole ( Hamdi et al, 1992 ; Auer et al, 2017 ) but to our knowledge no information could be found concerning other type of insects implemented in bioreactors.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the purpose of pretreatment, chemical, biological, thermochemical, or thermophysical methods are used, sometimes in combination [ 105 , 106 ]. After lysis of the cells the macromolecules of sugars need saccharification which mean to break the α-(1 → 4), α-(1 → 6), β-(1 → 3) and β-(1 → 6) glycosidic linkages between the monomers to release the monomers units [ 107 ]. Lignocellulose present in the biomass impedes the pretreatment process, as this material is recalcitrant to conversion.…”
Section: Pretreatment Of Algal Biomassmentioning
confidence: 99%
“…These findings were covered extensively in several recent reviews (11-13, 36, 112-114, 151). This topic is thus not covered further in this review; however, some key recent advances relating to novel symbiont sequencing protocols and feedstock digestion have been reported (81,97,104,105).…”
Section: Lignocellulose Bioconversionmentioning
confidence: 99%